Acreage Response and Production Stability of Sugarcane Crop in Ganganagar District of Rajasthan - Joshi, B R; Gajja, B L; Kalla, Jagdeesh C (Annals of Arid Zone, 2016)
The price structure of farm commodities influenced most of commercial output decisions. Sugarcane is one of the most important commercial crops which is generally immune to the forces of subsistence. Recently, the variability in production of sugarcane has created considerable problems of planning resource allocation for country's sugar industry. Arid region of western Rajasthan is traditionally not a sugarcane area. However, with the advent of canal irrigation, this crop has assumed a considerable commercial importance in the existing crop product-mix in the district like Ganganagar. To verify the existence of cobweb phenomenon, the alternative forms of cobweb models were generated. The results revealed that area allocation for sugarcane reveal cobweb phenomenon with convergent tendencies and amplitude for four to five years.